2002
DOI: 10.1302/0301-620x.84b5.0840688
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on outcome after operation for the carpal tunnel syndrome

Abstract: Decompression of the carpal tunnel is a common surgical procedure. Although the incidence of the carpal tunnel syndrome increases with age, there is no clear information available on the outcome of surgery in relation to age. We studied prospectively 87 consecutive patients who underwent decompression, using a validated self-administered questionnaire, and found that improvement in symptoms and function decreased with increasing age. This was most marked in patients over the age of sixty years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 0 publications
5
58
2
1
Order By: Relevance
“…Porter et al 3 reported that carpal tunnel surgery in older patients has worse results than in younger patients and Hobby et al 5 reconfirmed that older patients were more troubled postoperatively by reduced sensation compared with younger patients. Our results would suggest that the explanation for some of the patients in the older group having less satisfactory outcomes following surgery may be found in the statistically more severely affected conduction speeds both for the motor as well as the sensory conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porter et al 3 reported that carpal tunnel surgery in older patients has worse results than in younger patients and Hobby et al 5 reconfirmed that older patients were more troubled postoperatively by reduced sensation compared with younger patients. Our results would suggest that the explanation for some of the patients in the older group having less satisfactory outcomes following surgery may be found in the statistically more severely affected conduction speeds both for the motor as well as the sensory conduction.…”
Section: Discussionmentioning
confidence: 99%
“…1 For those patients who do respond satisfactorily to conservative measures, surgical decompression is often successful. 2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no objective explanation has been suggested for these observations.…”
mentioning
confidence: 99%
“…6,7) While treatment options for CTS include splinting, 8) oral glucocorticoids 9) and local steroid injections, 10) surgical decompression remains the definitive treatment for CTS. 11) Published literature has revealed a plethora of factors that influence the outcome of carpal tunnel release, amongst which include age, 12) gender, 13) severity of CTS 14) and presence of medical comorbidities. 15) Hitherto, we do not know of any study in existing published literature that examines the effect of hand dominance on the outcome of carpal tunnel release.…”
Section: Discussionmentioning
confidence: 99%
“…But there are a number of factors associated with poor outcome and patient satisfaction following carpal-tunnel decompression. These factors include diabetes, high age, double crush syndrome, and severity of preoperative symptoms [2,[4][5][6][11][12][13]. General factors associated with poor satisfaction are alcohol abuse, poor mental-health status and involvement of a lawyer [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that are known to influence the outcome of the surgery. These factors include age, duration of symptoms, alcohol use, mental-health status, and presence of objective neurological deficit [2,[4][5][6][7][11][12][13].…”
Section: Introductionmentioning
confidence: 99%